2020
DOI: 10.1007/s00394-020-02282-5
|View full text |Cite|
|
Sign up to set email alerts
|

Prebiotic effect of inulin-type fructans on faecal microbiota and short-chain fatty acids in type 2 diabetes: a randomised controlled trial

Abstract: Purpose Compared to a healthy population, the gut microbiota in type 2 diabetes presents with several unfavourable features that may impair glucose regulation. The aim of this study was to evaluate the prebiotic effect of inulin-type fructans on the faecal microbiota and short-chain fatty acids (SCFA) in patients with type 2 diabetes. Methods The study was a placebo controlled crossover study, where 25 patients (15 men) aged 41–71 years consumed 16 g of inulin-type fructans (a mixture of oligofructose and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(96 citation statements)
references
References 59 publications
1
82
3
2
Order By: Relevance
“…The characteristics of the studies included are shown in Table 2 . While three of these studies were conducted in Italy [ 26 , 27 , 28 ], one study each was carried out in Norway [ 29 ], Japan [ 30 ], Mexico [ 22 ], UK [ 23 ], Canada [ 31 ] and China [ 13 ]. All the studies were randomised controlled trials with parallel design, except one which was a randomised cross-over study [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the studies included are shown in Table 2 . While three of these studies were conducted in Italy [ 26 , 27 , 28 ], one study each was carried out in Norway [ 29 ], Japan [ 30 ], Mexico [ 22 ], UK [ 23 ], Canada [ 31 ] and China [ 13 ]. All the studies were randomised controlled trials with parallel design, except one which was a randomised cross-over study [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, there were no significant differences in alpha or beta diversity [ 31 ]. According to Birkeland et al [ 29 ], in the dietary fibre group, there was moderate changes in the faecal microbiota composition (1.5%, p = 0.045), and the effect was most prominent on operational taxonomic units (OTUs) of Bifidobacterium adolescentis, followed by OTUs of Bacteroides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease of phylum Bacteroidetes was mainly due to the poor abundance of Bacteroides in the DM group at the genus level. Bacteroides was famous for its genomic capability, which could ferment various sugars into short-chain fatty acids (SCFAs) [ 9 ]. Among SCFAs, propionic acid could reduce visceral fat.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, ndings concerning the effect of dietary bre intake on butyrate level are inconsistent across different studies. The intake of inulin-type fructans by patients with type 2 diabetes showed unchanged level [27], whereas inulin intake by mice showed the increasing level of butyrate in faeces, but not in plasma [28]. Alfalfa-containing diet also increased butyrate level in the caecal digesta of pigs [29] and caecal levels of mucosal genes involved in SCFA sensing and absorption [29].…”
Section: Discussionmentioning
confidence: 99%